Combining targeting methodologies for better targeting of the extreme poor: some preliminary findings from BRAC's CFPR/TUP programme - Matin, Imran; Halder, Shantana R. (BRAC, 2019)
Since January 2002, BRAC has started a new program targeted at the extreme poor, called, 'Challenging the Frontiers of Poverty Reduction: Targeting the Ultra Poor' (CFPR/TUP). This Programme seeks to challenge the frontiers of poverty reduction by addressing two key limitations of much poverty reduction interventions to date. First, the Programme seeks to 'push down' the reach of development programmes through specific targeting of the ultra poor who have suffered relative neglect in most development programme interventions to date. Secondly, it seeks to 'push out' the domain within which existing approaches operate, by addressing dimensions of poverty that many conventional approaches fail to address. Specifically, this involves a shift away from the conventional service delivery mode of development programming to focussing on human capital, and the structures and processes that disempower the poor, especially women, and constraint their livelihood. It is an approach that puts social development, specifically a rights-based approach to health and socio-political empowerment, at the heart of the agenda. This paper has two objectives. The first is an introduction of the new BRAC Programme that aims to experiment with a different type of approach to attacking extreme poverty. More specifically, the focus in this paper is to introduce the targeting methodology used in this Programme. The underlying theme of both the CFPR/TUP Programme and the targeting methodology it used is an acknowledgment of the power and strength of combining methods and approaches and thereby leveraging each other. The Programme for instance combines promotion and protection oriented mechanisms to attacking poverty and uses this mix at various levels acknowledging the idea that the structures that create and reproduce poverty work at multiple levels. Similarly, the targeting approach used in the Programme also combines various targeting methodologies and knowledge streams about who the extreme poor are and where they live. The second objective of this paper is to use Programme data emerging out of the targeting exercise to undertake preliminary exploration of questions of effectiveness of the approach used. The combining of various targeting approaches and drawing from different streams of knowledge has been the main innovativeness of the targeting methodology used in the CFPR/TUP programme. The close correspondence between community perception of the variables distinguishing the extreme poor from the other wealth groups and what the Programme developed based on reading of existing poverty profile literature of Bangladesh points to the maturity and evolution of formal, more academic knowledge on poverty profile in being able to capture the categories and descriptions used by poor people themselves. This is encouraging. What is needed now is moving beyond more grounded poverty profile to more grounded understanding of the various mechanisms through which poverty persists for some and not for others and what can be done about it. However, the big differences between the two closely ranked groups of the poor-the extreme poor and those just above, also suggest that there is a structural break, rather than a continuum in terms of deprivation of opportunities, security and empowerment that is differentiating the extreme poor from others. It is through a better understanding of the various dimensions, dynamics and interlinkages of these structural breaks can we design the most effective strategies and programmatic approaches for this group.